Beginning Spring 2 - Minter, Dave (Apress, 2012)
The Spring framework is a stunningly good piece of software. Building enterprise software is a difficult exercise at the best of times, and there are numerous common problems that developers consistently encounter. Spring smooths over or eliminates a remarkable number of these problems. Spring’s clean design and accommodating approach to existing standards and libraries has resulted in a spectacular rise in its popularity among Java developers. Spring can be retrofitted to old projects and is now often used as the foundation for new development. If you haven’t yet encountered Spring, you probably will do so very soon. Although Spring is well designed and documented, getting bootstrapped in the basics of the framework can still be difficult. This book aims to get Java developers up and running with Spring as quickly as possible by tying the abstract and conceptual discussions to concrete examples in code.